Music, mind, and embodiment : 11th International Symposium, CMMR 2015, Plymouth, UK, June 16-19, 2015, Revised selected papers /: 11th International Symposium, CMMR 2015, Plymouth, UK, June 16-19, 2015, Revised selected papers. (2016) - Unknown
No abstract available